Does Repetition Matter? Analysis of Biology Majors’ Ability to Comprehend Journal Articles Across a Major - Raimondi, Stacey L. (J Microbiol Biol Educ, 2020)
The ability to read and critically analyze the primary literature is a core skill necessary for future success in scientific fields. While many studies have described methodologies to teach journal reading, no studies examine how much practice and repetition is required before students learn how to comprehend a journal article. Here we assessed student journal reading and comprehension throughout an undergraduate biology major, analyzing students in six upper-level elective courses, some of which had no journal reading requirements while others had extensive requirements built into the course. We hypothesized that there would be a strong correlation between number of articles read in a semester and student ability to comprehend the articles, as well as their comfort and confidence with journal reading. Surprisingly, we found that the number of articles required for a class did not affect overall student reading comprehension and critical thinking even though students self-assessed that they gained comfort and confidence with articles as the number increased. Instead, we found that sophomore students in their first upper-level biology course showed significant gains in learning when the course activities include journal article readings. After this initial gain, there were no significant learning gains in future years, no matter the number of journals required in the course. Together, the results shown here indicate that it is not necessary to revise an entire curriculum to improve students’ journal reading and critical thinking skills. Instead, early intervention and exposure to critical journal article reading is most important for this skill development.